Information Systems Audit Based on ISO 9001: 2015 in Depaterment Library and Archives Salatiga - eko nur hermansyah (International Journal of Science, Engineering, and Information Technology, 2018)
Information system audit was carried out in the Salatiga Regional Library and Archives, using the ISO 9001: 2015 standard method, focusing on environmental control, physical control, logical controls, and IS operation, to obtain results. Libraries already have the distribution of access rights to users, already have policies that regulate it, and already have security in accordance with standards. Based on the results of the audit of the asset management information system that was done late, it was obtained a statement that the library has never conducted an information system audit of the performance of the information system it has to ensure the performance of the existing information system based on ISO 9001: 2015 standards.